Westonci.ca is your go-to source for answers, with a community ready to provide accurate and timely information. Discover comprehensive answers to your questions from knowledgeable professionals on our user-friendly platform. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.
Sagot :
To find the inverse of the function [tex]\( f(x) = \frac{\sqrt{x-2}}{6} \)[/tex], we follow a step-by-step process:
1. First, express [tex]\( y \)[/tex] in terms of [tex]\( x \)[/tex]:
[tex]\[ y = \frac{\sqrt{x-2}}{6} \][/tex]
2. Switch [tex]\( x \)[/tex] and [tex]\( y \)[/tex] to begin finding the inverse:
[tex]\[ x = \frac{\sqrt{y-2}}{6} \][/tex]
3. Clear the fraction by multiplying both sides by 6:
[tex]\[ 6x = \sqrt{y-2} \][/tex]
4. Square both sides to eliminate the square root:
[tex]\[ (6x)^2 = y - 2 \][/tex]
[tex]\[ 36x^2 = y - 2 \][/tex]
5. Solve for [tex]\( y \)[/tex] by adding 2 to both sides:
[tex]\[ y = 36x^2 + 2 \][/tex]
Thus, the inverse function is:
[tex]\[ f^{-1}(x) = 36x^2 + 2 \][/tex]
Among the given choices:
A. [tex]\( f^{-1}(x) = 36 x^2 + 2 \)[/tex], for [tex]\( x \geq 0 \)[/tex]
B. [tex]\( f^{-1}(x) = 6 x^2 + 2 \)[/tex], for [tex]\( x \geq 0 \)[/tex]
C. [tex]\( f^{-1}(x) = 36 x + 2 \)[/tex], for [tex]\( x \geq 0 \)[/tex]
D. [tex]\( f^{-1}(x) = 6 x^2 - 2 \)[/tex], for [tex]\( x \geq 0 \)[/tex]
The correct answer matches our derived inverse function. Therefore, the correct answer is:
A. [tex]\( f^{-1}(x) = 36 x^2 + 2 \)[/tex], for [tex]\( x \geq 0 \)[/tex].
1. First, express [tex]\( y \)[/tex] in terms of [tex]\( x \)[/tex]:
[tex]\[ y = \frac{\sqrt{x-2}}{6} \][/tex]
2. Switch [tex]\( x \)[/tex] and [tex]\( y \)[/tex] to begin finding the inverse:
[tex]\[ x = \frac{\sqrt{y-2}}{6} \][/tex]
3. Clear the fraction by multiplying both sides by 6:
[tex]\[ 6x = \sqrt{y-2} \][/tex]
4. Square both sides to eliminate the square root:
[tex]\[ (6x)^2 = y - 2 \][/tex]
[tex]\[ 36x^2 = y - 2 \][/tex]
5. Solve for [tex]\( y \)[/tex] by adding 2 to both sides:
[tex]\[ y = 36x^2 + 2 \][/tex]
Thus, the inverse function is:
[tex]\[ f^{-1}(x) = 36x^2 + 2 \][/tex]
Among the given choices:
A. [tex]\( f^{-1}(x) = 36 x^2 + 2 \)[/tex], for [tex]\( x \geq 0 \)[/tex]
B. [tex]\( f^{-1}(x) = 6 x^2 + 2 \)[/tex], for [tex]\( x \geq 0 \)[/tex]
C. [tex]\( f^{-1}(x) = 36 x + 2 \)[/tex], for [tex]\( x \geq 0 \)[/tex]
D. [tex]\( f^{-1}(x) = 6 x^2 - 2 \)[/tex], for [tex]\( x \geq 0 \)[/tex]
The correct answer matches our derived inverse function. Therefore, the correct answer is:
A. [tex]\( f^{-1}(x) = 36 x^2 + 2 \)[/tex], for [tex]\( x \geq 0 \)[/tex].
Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. We appreciate your time. Please revisit us for more reliable answers to any questions you may have. Westonci.ca is your trusted source for answers. Visit us again to find more information on diverse topics.